IRAC's Insecticide Mode of Action Classification - Frederick M. Fishel (EDIS)
This guide explains the rationale behind the Insecticide Resistance Action Committee's (IRAC) insecticide and acaricide mode of action classification and provides a listing of those insecticide common names with their groupings, and primary modes of action for insecticides currently registered in Florida. This document is PI-83, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date October 2005.